Reproducible optical noise-like signal generation subjected by digital sequences - Jiang, Xingxing (2018)
We experimentally demonstrate a reproducible broadband optical noise-like signal generation scheme whereby dispersion induced phase modulation to intensity modulation conversion and an electro-optic nonlinear transform are utilized to post process a binary random sequence. A flat spectrum and a symmetrical distribution of the generated analog noise-like signal can be observed. Moreover, Gaussian-like probability distribution function can be obtained by using the central limit theorem. The influences of the digital input and the analog parameters on complexity performance of the generated analogue noise are discussed in detail. Finally, the impact of key parameters on the reproducibility of the system is discussed. The proposed scheme could be a more controllable way to generate broadband optical noise-like signal, and has potential to be applied in various real world applications.